Technology selection for cultivation of sunflower hybrids in Central Black Earth region - Zasorina Elsa (EDP Sciences, 2021)
This study applies a number of technologies to cultivation of sunflower hybrids with variable soil properties, weather conditions and farm locations in Central Black Earth: Kursk, Orel and Voronezh regions. The three-year research identified reactions of sunflower hybrids from different manufacturers to cultivation technology and weather conditions; we made relevant observations; analysed yield structure, yield and seed quality parameters; forecast prospects of using CLEARFIELD and ExpressSun technologies for sunflower cultivation in Central Black Earth region. Overall, the experiment revealed the advantage of CLEARFIELD® (EURO-LIGHTNING®) technology in Kursk region. Hybrids from main producers had a superior average result compared to the standard hybrid SI Bacardi (Syngenta) over three years of research: this is an increase of 0.6 t/ha or 24% (hybrid P64LC108), 1.3 t/ha or 52% (hybrid EC Generalis), and 0.9 t/ha or 36% (hybrid MAS 89 IR).In Orel region hybrids cultivated with ExpressSun (Express® 75 v.y.) or Sumo showed better performance. The hybrid P62LE122 gave an increase of 0.4 t/ha or 20% and the hybrid EC Argentic - 0.3 t/ha or 15% compared to the standard hybrid Sumiko (Syngenta). In Voronezh region hybrids cultivated by ExpressSun (Express ® 75 v.y.) or Sumo technology had yield advantage. Increases were between 0.5 and 1.0 t/ha, or between 15 and 29%, depending on the sunflower hybrid cultivated